The effect of school culture, leadership, and teacher competence on teacher performance in cluster 05, Padarincang District - Lihah Muflihah; Ani Wulandari Sumardi; Encun Sunardi; Dedeh Kurniasih; Priatna Wijaya (Enrichment : Journal of Management, 2026)
This study examined the effects of school culture, principal leadership, and teacher competence on the performance of elementary school teachers in Cluster 05 of Padarincang District. Using a quantitative correlational survey design, the research involved all 87 teachers from public elementary schools in the cluster through a saturated sampling technique. Data were collected through literature review, field observations, and structured questionnaires employing a five-point Likert scale. Prior to hypothesis testing, the research instruments were tested for validity and reliability, and classical assumption tests—covering normality, multicollinearity, and heteroscedasticity—were conducted to ensure the suitability of the regression model. The data were then analyzed using multiple linear regression. The results indicate that school culture, principal leadership, and teacher competence each have a positive and statistically significant effect on teacher performance, both individually and simultaneously. Among these variables, school culture emerged as the most influential factor. The Adjusted R Square value of 0.523 shows that 52.3% of the variation in teacher performance is explained by the three variables, while the remainder is influenced by factors outside the model. These findings highlight the importance of strengthening school culture, enhancing leadership quality, and continuously developing teacher competencies to improve educational outcomes